Increased Bone Mineral Content During Rapid Weight Gain Therapy in Anorexia Nervosa - Tubić, B.; Pettersson, C.; Svedlund, A.; Forslund, H. Bertéus; Magnusson, P.; Swolin-Eide, D. (Hormone and Metabolic Research, 2016)
Patients with anorexia nervosa (AN) are at high risk of reduced bone mass. Osteocalcin (OC), a bone formation marker, has been proposed to act as a link between bone and energy metabolism. We investigated how the 3 forms of OC respond during a 12-week intensive nutrition therapy in AN patients, in whom large changes in energy metabolism are expected.Twenty-two female AN patients, mean 20.9 years of age, with a starting mean body mass index (BMI) 15.5 kg/m2 (minimum-maximum) (13.4–17.3 kg/m2) completed the study. Biochemical markers, body composition, bone mass by DXA, and pQCT were assessed. Subjects gained in median 9.9 kg (5.5–17.0 kg), and BMI increased from median 15.4 kg/m2 (13.4–17.3 kg/m2) to 19.0 kg/m2 (16.2–20.6 kg/m2), p<0.0001. Fat mass increased from median 11.4% (4.4–24.8%) to 26.7% (16.9–39.8%). Total OC, carboxylated OC (cOC), undercarboxylated OC (ucOC), and bone-specific alkaline phosphatase (BALP) increased during the study period. No change was observed for the resorption marker carboxy-terminal cross-linking telopeptide of type I collagen (CTX). Total body bone mineral content (BMC) increased, but no changes were found for whole body or lumbar spine bone mineral density. Tibial trabecular density measured by pQCT decreased. Total OC, cOC, and ucOC were not associated with BMI, insulin or body composition parameters. This prospective study demonstrates that all 3 forms of OC (total OC, cOC, ucOC) increase during rapid weight gain. BALP increased while the resorption marker CTX was unchanged, which corroborate with the increased total body BMC.
Keywords: eating disorder; markers of bone turnover; bone mineral density; body composition; adiponectin; osteocalcin